The Elusive Meaning of Religious Equality - Robin Charlow (Washington University Law Quarterly, 2005)
Raging national debates about the relationship of church and state often find parties sparring over whether the government is treating religious interests equally. This Article endeavors to explain why there is such widespread disagreement about the meaning of religious equality. It explores both jurisprudential and doctrinal sources of dispute, including: the multidimensional nature of equality generally, the uniqueness of religion, the difficulty of defining religion, and the problem of identifying the proper baseline or point of comparison for assessing religious equality. Ultimately, we cannot separate issues of religious equality from disputes about the meaning of the Constitution's religion clauses. The Article presents the thesis that, on a collective level, we may suffer from a long-standing, national uncertainty or ambiguity about religion and the ideal relationship between church and state, accounting in part for our endless conflict over the meaning of the religion clauses. The Article concludes by examining whether it is possible to resolve or avoid questions of religious equality and, if not, what useful lesson can be drawn from our uncertain history.
Keywords: Establishment clause (Constitutional law); Free exercise clause (Constitutional law); Equality; Freedom of religion -- Constitutional history; Church and state; Equal protection; United States